Encuesta de calidad de vida 2003 CAPÍTULO TELEVISIÓN - -CEO-, Centro de Estudios de Opinión (La Sociología en sus Escenarios, 2009)
Abstract The TV is a necessary good. The possession and the consumption of the TV highly are related to the spending power of the home. The level of cap of the private channels surpasses the channels significantly public. The Profile of the viewer difference by type of channel, hour strip and type of programming, thus: Channels Public: Adults and minor layer. Nevertheless, Colombia Signal breaks with this scheme. Private channels: Its penetration is so high that it covers all the segments with the population. At strip level: Tomorrow: Layer low and young people Noon: Age superior to 25 years Behind schedule: Layer low and young people Night: Layer Strip of afternoon of the Weekend: Relative Programming: News: High layer and adult Entertainment: Low layer and young Channels of National Operation: Preference by reporters and soap operas Channels of Operation the International: Preference by Films, Documentary and Opinion Resumen La TV es un bien necesario. La tenencia y el consumo de la TV están altamente relacionados con el poder adquisitivo del hogar. El nivel de cubrimiento de los canales privados superan significativamente los canales públicos. El Perfil del televidente se diferencia por tipo de canal, franja horaria y tipo de programación, así: Canales Públicos: Adultos y menor estrato. Sin embargo, Señal Colombia rompe con este esquema. Canales Privados: Su penetración es tan alta que cubre todos los segmentos de la población. A nivel de franja: Mañana: Estrato bajo y gente joven Medio Día: Edad superiores a 25 años Tarde: Estrato bajo y gente joven Noche: Estrato Franja de la tarde del Fin de Semana: Familiar Programación Informativos: Estrato alto y adultos Entretenimiento: Estrato bajo y jóvenes Canales de Operación Nacional: Preferencia por noticieros y telenovelas Canales de Operación Internacional: Preferencia por Películas, Documentales y Opinión